Unconcealment and the Nature of Creation. On the Relation between Technology and Nature in Heidegger’s Philosophy - A S Nikulina (RUDN Journal of Philosophy, 2018)
The article elaborates on two significant notions of Heidegger’s philosophy - “production” and “creation” - representing different ways in which being and Dasein relate to each other. We show that the process of creation is rooted in a “non-metaphysically” understood concept of nature, that is, in the kinetic character of being, which is essentially different from the understanding of being as eidos. If nature is seen as “being as such”, as the source of any creation and any relation (and the possibility of relation), then “technical” dimension becomes a part of natural process, opening a prospect of a new understanding of technology in communion with poetry and thought.